(untitled) (Global Journal of Science Frontier Research, 2012)
The study assessed farmers’ technologies on integrated and non integrated fish farming in Ogun State Nigeria. Multi stage Random sampling techniques was used to select 133 non -integrated fish farmers (NIFF) and 216 integrated fish farmers (IFF) (n = 349) from the study area. Data were analysed using chi-square, T-test and Pearson Product moment correlation. Results showed that 92.5% of NIFF were male compared to IFF (90.7%). Also, 96.8% of IFF and 79.7% of NIFF were married. The mean ages of sampled farmers were 44 years (NIFF) and 46 years (IFF) while the mean fish farming experiences were 4 years (NIFF) and 5 years (IFF). More so, 99.1% of IFF identified pond site selection as one of the key technologies used in integrated fish farming compared to 95.5% recorded for NIFF.